Analysis of Job Satisfaction in Mediating Employee Retention and Self Efficacy Towards Turnover Intention - Riza Salma Syari; Ihwan Susila; Jati Wakito (Indonesian Journal of Business Analytics, 2025)
This research seeks to examine the function of job satisfaction as a mediating factor in the association between employee retention and self-efficacy with turnover intention. Employing a quantitative research design, the study utilized the Partial Least Squares-Structural Equation Modeling (PLS-SEM) technique for data analysis. A total of 256 participants were recruited through a simple random sampling procedure. The findings indicate that neither employee retention nor self-efficacy exerted a significant direct impact on turnover intention. However, both variables demonstrated a positive and statistically significant effect on job satisfaction. Furthermore, job satisfaction was found to negatively and significantly influence turnover intention, effectively mediating the relationship between employee retention and self-efficacy and employees’ intention to leave the organization. These findings confirm that job satisfaction has a significant role in suppressing employee intentions to leave the company. Future research is recommended to use mixed methods and consider external factors such as organizational commitment, job stress, and the work environment.